Poor Richard's Legacy: American Business Values from Benjamin Franklin to Michael Milken. - Morgan, Robert G.; Moriarity, Shane R. (The Accounting Review, 1992)
Reviews the book "Poor Richard's Legacy: American Business Values From Benjamin Franklin to Michael Milken," by Peter Baida.